The translation strategy of idioms from English into Indonesia: The Blind Side movie - Dewy Shynta, Dewy Shynta; Lantu, Ika Paramitha; Yuliana Dg. Macora (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This research aims to find out the translation strategies of idioms found in the Blind Side movie. Baker (1992) and Newmark (1988) are the theories use for the research. This research is a qualitative research method. The data in this research are the movie script and the movie subtitles. The results show that there are seven idioms and one type of translation strategy found in the movie. The translation strategy is translation by paraphrase.